Potentiel et obstacles à l'appropriation d'un parcours de formation « hybride » - Teresa Assude (Centre National d'Enseignement à Distance, 2012)
Pairform@nce is a "hybrid" teachers training device aiming at the development of teachers' professional skills of ICT integration. What is the potential of such training courses? What are the conditions and the obstacles to their appropriation? These two questions will be approached by the analysis of four of such courses and by taking the point of view of the actors (teachers and trainers).